CONTENT INTERRELATIONSHIP OF OXYMORON COMPONENTS (Scientific journal of the Fergana State University, 2025)
The semantic connection between the parts of the oppositional syntactic-stylistic figure in our language, as well as their logical connection and their function in the text, that is, feelings, internal experiences, the mental state of the characters and the conflict situations that arise. The features of expression were studied in it.